REPAIR OF BURNT DEFECTS IN CGB (CORRECTED GRAIN BOX) ARTICLES THROUGH THE FINISHING PROCESS - Mita Ristanti; Nurwantoro; Nais Pinta Adetya (Politek ATK Yogyakarta Press, 2023)
The purpose of this study was to repair Corrected Grain Box (CGB) leather which had burnt defects through a finishing process so that the finished leather could meet SNI 0234:2009 standards. The material used is CGB finish cowhide leather with reject quality for 1 side with an area of ​​16.50 sqft and a thickness of 1.76 mm as raw material. The chemicals used are stucco, flesh side binder, compact binder, soft resin compact, copolymer binder, adhesion, filler, acrylic binder, pigment, lacquer, thinner, and silicon. The research process consists of two stages, namely the implementation of the finishing process and testing. The finishing process includes coarse buffing, stucco, fine buffing, spray backside or flesh side, ironing, roll coating 1 (base coat), spray lacquer solvent 1, emboss sandblast 1, roll coating 2 (medium coat), spray lacquer solvent 2, staking, embossing sandblast 2 and measuring. The finish results of the CGB skin obtained were skin which initially had a burned defect area of ​​82%, after repairs the area of ​​the defect was reduced to <10%. Organoleptic testing consisted of color evenness and nerf release, while physical tests, namely the rubbing resistance of wet and dry paint, were carried out and all the results met the SNI 0234:2009 standard.